PREDICTIVE VALUE OF INTERLEUKIN-22 AND INTERLEUKIN-17А LEVELS IN YOUNG CHILDREN WITH RECURRENT URTICARIA - Максим Викторович Бондаренко; Тамара Анатольевна Сиротченко (The Publishing House Medicine and Enlightenment, 2022)
The aim of the research - to determine the prognostic value of IL-22, IL-17A of young children with recurrent acute urticaria as criteria for the severity of atopic dermatitis. Materials and methods. We analyzed the results of examination of 67 children with atopic dermatitis aged 1 to 3 years with a history (anamnesis) of atopic dermatitis, the length of the underlying disease for at least 6 months, the presence of at least two episodes of acute urticaria in the history. The concentration levels of IL-22, IL-17A were determined. Results. Significant changes in cytokines of children with atopic dermatitis take place and, based on their results, the severity of the disease can be predicted. Conclusion. The identification of known and the discovery of new interleukins in various diseases is important for determining the severity of the disease and predicting the development of the disease.